Strategi Promosi dalam Meningkatkan Penjualan Mousse Cake pada Toko Kue Le Chic Bakehouse Medan - Ayu Zulika Handayani; Achmad Zulfikar Siregar; Annisa Lestari (Yayasan Literasi Sains Indonesia, 2022)
This research aims to find out the promotional strategy carried out by the Le Chic Bakehouse Medan cake shop in increasing its sales. This study uses a qualitative approach where the data collection techniques include observation, interviews, documentation, and literature study. The data analysis technique used consists of several stages starting from data collection, data reduction, data presentation, and concluding. From the results of the study, it was explained that Le Chic Bakehouse Medan had implemented five promotional mix strategies, which included advertising strategies by collaborating with Grabfood, Gofood, Shopeefood, Instagram, and Google Maps. Sales promotion strategy by providing discounts, buy one get one, appeal, and giveaway. The strategy of personal selling (personal selling) uses the word-of-mouth method. Public relations and publicity strategy by collaborating with large companies, one of which is Bank Mandiri. Direct marketing strategy serves customers directly from the store or via telephone, WhatsApp, and Instagram. The promotional strategy carried out by Le Chic Bakehouse Medan turned out to be very influential in increasing sales at the store.